VOLCANOLOGY AND FACIES ARCHITECTURE OF FLOOD BASALTS - Jerram D.A. (My University, 2002)
In terms of their detailed volcanology and facies architecture, continental flood basalts and associated volcanic rifted margins reveal important information to help our understanding of their evolution. Mafic volcanism, which makes up the majority of preserved material, is characterized by flows 2-3 m to several tens of meters thick, with ponded flows and occasional massive flow events of ∼100 m thick. Although most of the flows are emplaced by the same mechanism as passive inflated sheets, a variety of different facies associations are dependent on flow volumes and to some extent flow composition. The largest silicic volcanic events in continental flood basalts are larger in volume than the largest recorded mafic events, and they are potentially more catastrophic if erupted as ignimbrite flows. The architecture of continental flood basalts and associated volcanic rifted margins is recorded by facies types and facies associations. Facies types, such as tabular-classic flows, braided-compound flows, or hyaloclastites, represent genetically related building blocks of the volcanic stratigraphy. Facies associations, such as downlap, onlap, and disconformities, relate how the volcanic facies are stacked together. Many of the facies associations occur on an intermediate to large basin-wide scale and may only be revealed by detailed field work, photogrammetry, and three-dimensional geological models.